RESOLVING A REALISTIC MIDDLE GROUND TOWARDS THE SUSTAINABILITY TRANSITION IN THE GLOBAL POLITICAL AND ECONOMIC LANDSCAPE: A COMPREHENSIVE REVIEW ON GREEN CAPITALISM: Received: 27th July 2023; Revised: 27th October 2023, 06th November 2023; Accepted: 22nd November 2023 - Triana Budiono, Syabella (PEOPLE: International Journal of Social Sciences, 2024)
In 2019, a climatic wake-up call was made by the IPCC as the world’s temperature is projected to increase by 4-6°C. With the systematically ingrained capitalist imperatives in the political and economic landscape, the notion of “green capitalism” was introduced in the justification of limitless economic growth with less energy consumption than the world can sustainably produce (Schweickart, 2010). Prior research has identified heterogenous stances on green capitalism. However, sustainable transition research has neither clarified the realistic middle ground that it should pursue, nor has it determined whether a pro- or anti-capitalistic stance should be taken in the first place (Feola, 2020). Through a literature review, the analysis of heterogeneous stances on green capitalism based on its debate scopes reveals the need to exploit capitalist imperatives to a sustainably appropriate extent rather than forcing it to produce a midway standpoint of the “Net Zero” global consensus. The findings suggest the need for a potential reconceptualization of capitalism in the political and economic landscape as a tool of green revolution toward sustainable transition, providing a realistic middle ground.